Psychosocial Experiences of African Migrants in Six European Countries A Mixed Method Study - Idemudia, Erhabor (Social Indicators Research Series, 2020)
This open access book provides an empirical account of the psychological and social experiences of 3500 African migrants to 6 European countries: Germany, Spain, Italy, The Netherlands, France, and the UK. It discusses the psychosocial motivations for migration from Africa, who migrates where, and stressful pre- and post-migration factors affecting the social and psychological wellbeing of migrants. The book also includes a detailed exploration of posttraumatic stress disorder (PTSD) and posttraumatic stress symptoms (PTSS) among African migrants. Addressing and offering solutions to pre- and post-migration problems in Africa and Europe as well as the problems associated with the perilous journeys involved, this unique study is a must-read for anyone interested in cross-cultural psychology and social science, and particularly in migration and mental health.